Impact of rain weather over free space optic communication transmission - A.K Rahman; N Julai; M. Jusoh; C.B.M Rashidi; S.A Aljunid; Anuar M.S; M.F Talib; Nurdiani Zamhari; S.K Sahari; K.F. Tamrin; Rudiyanto P. Jong; D.N.A Zaidel; N.A.A Mohtadzar; M.R.M Sharip; Y.S Samat (Institute of Advanced Engineering and Science, 2019)
This paper focuses the rain effect over FSO link medium in Malaysia environment. In this work, a rain data samples that collected from Malaysian Meteorological Department (MMD) to determine the scattering coefficient, atmospheric attenuation and total attenuation. From the analysis, the precipitation rate give different impact over FSO link which can cause the attenuation and bit error rate increase. The results also show the comparison parameter for optimal geometrical loss such as beam divergence, aperture size and receiver sensitivity.